RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA SAMPAH (PLTSa) DI LINGKUNGAN STT MIGAS BALIKPAPAN - Nurjanah Nurjanah; A.M. Miftahul Huda; Riza Hadi Saputra; Ain Sahara; Hasanudin Hasanudin (PETROGAS: Journal of Energy and Technology, 2021)
The Environment and Forestry Metrics stated that data on waste piles in Indonesia in 2020 reached 67.8 tons, 45% of which was poorly managed plastic waste. The large amount of waste produced causes Indonesia to become the second waste producer in the world. The level of waste management that is still minimal is the main thing that causes Indonesia to become a "polluting" country in the world. Waste Power Plant is a waste management solution to reduce the amount of waste and become an alternative energy for generating electricity in the community. The purpose of this research is to provide an alternative by creating a waste power plant as a producer of renewable electrical energy. This research begins with collecting materials and continues with the design of components such as furnaces, boilers, steam turbines, DC generators which are integrated into one, and waste as fuel. The components that have been worked are then tested with plastic waste and wood waste are collected and then put into the furnace, then the waste is burned to boil water in the boiler. Changes in the speed or relative velocity of this steam cause a force turns the turbine. The turbine that is connected to this generator will then rotate the generator to produce electricity. Based on the results of testing the solid waste power plant, the maximum voltage value is 13.76 V.